The Influence of M-Commerce Ubiquity and Web Design on Brand Trust M-Commerce Usage Behavior in QRIS Application Users Moderated by Product Reputation - H. Nababan, Poltak Haben; Kurniawati (Fakultas Ekonomi & Bisnis Universitas Muslim Indonesia, 2025)
The purpose of this research is to analyze the influence of M-Commerce Ubiquity and Web Design on Brand Trust and M-Commerce Usage Behavior on Qris application users moderated by Product Reputation. Data collection for this study was carried out by filling out questionnaires periodically and online. The number of respondents who were successfully obtained and processed the data was 231 respondents. Research respondents are users who make payments with Qris. The tool used for data processing is Amos. The results of this study indicate that M-Commerce Ubiquity has no effect on Brand Trust, Web Design has a positive effect on Brand Trust, Brand Trust has a positive effect on M-Commerce Usage Behavior, M-Commerce Ubiquity has a positive effect on M-Commerce Usage Behavior mediated by Brand Trust, and Product Reputation moderates the effect of Brand Trust on M-Commerce Usage Behavior is not supported.